Accurate isolation and detection of circulating tumor cells using enrichment-free multiparametric high resolution imaging - Yeo, Dannel; Kao, Steven; Gupta, Ruta; Wahlroos, Sara; Bastian, Althea; Strauss, Heidi; Klemm, Vera; Shrestha, Prajwol; Ramirez, Arturo B.; Costandy, Lillian; Huston, Ryan; Gardner, Brady S.; et al. (Frontiers in Oncology, 2023)
Introduction: Reliable and accurate detection of rare circulating tumor cells (CTCs) from cancer patient blood samples promises advantages in both research and clinical applications. Numerous CTC detection methods have been explored that rely on either the physical properties of CTCs such as density, size, charge, and/or their antigen expression profiles. Multiple factors can influence CTC recovery including blood processing method and time to processing. This study aimed to examine the accuracy and sensitivity of an enrichment-free method of isolating leukocytes (AccuCyte® system) followed by immunofluorescence staining and high-resolution imaging (CyteFinder® instrument) to detect CTCs. Method: Healthy human blood samples, spiked with cancer cells from cancer cell lines, as well as blood samples obtained from 4 subjects diagnosed with cancer (2 pancreatic, 1 thyroid, and 1 small cell lung) were processed using the AccuCyte-CyteFinder system to assess recovery rate, accuracy, and reliability over a range of processing times. Results: The AccuCyte-CyteFinder system was found to be highly accurate (95.0%) at identifying CTCs in spiked-in samples (in 7.5mL of blood), even at low spiked-in numbers of 5 cells with high sensitivity (90%). AccuCyte-CyteFinder recovery rate (90.9%) was significantly higher compared to recovery rates obtained by density gradient centrifugation (20.0%) and red blood cell lysis (52.0%). Reliable and comparable recovery was observed in spiked-in samples and in clinical blood samples processed up to 72 hours post-collection. Reviewer analysis of images from spiked-in and clinical samples resulted in high concordance (R-squared value of 0.998 and 0.984 respectively). Discussion: The AccuCyte-CyteFinder system performs as an accurate, sensitive, and clinically practical method to detect and enumerate CTCs. This system addresses some of the practical logistical challenges in incorporating CTCs as part of routine clinical care. This could lead to CTCs guiding patients for precision, personalized medicine.